2020
DOI: 10.1038/s41598-020-65776-6
|View full text |Cite
|
Sign up to set email alerts
|

On the Aggregation and Nucleation Mechanism of the Monoclonal Antibody Anti-CD20 Near Liquid-Liquid Phase Separation (LLPS)

Abstract: The crystallization of Anti-CD20, a full-length monoclonal antibody, has been studied in the PEG400/ na 2 So 4 /Water system near Liquid-Liquid Phase Separation (LLPS) conditions by both sitting-drop vapour diffusion and batch methods. In order to understand the Anti-CD20 crystallization propensity in the solvent system of different compositions, we investigated some measurable parameters, normally used to assess protein conformational and colloidal stability in solution, with the aim to understand the aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…B 22 and k d measured under dilution are generally considered as predictors of high concentration behavior. Nevertheless, the high concentration behavior may differ from the behavior observed under dilution conditions because the “crowding” effect, i.e., increased opportunities for molecular interactions, deviations from thermodynamic ideals, and higher order interactions (e.g., B 23 , B 222 ), can significantly alter the net protein–protein interaction. , On the basis of the experimental observation of LLPS in the nucleation region, the authors suggest that it is likely that only a small number of protein molecules distributed at the droplet interface can experience protein–protein short-range attraction interactions induced by local environmental factors, without affecting the average B 22 value …”
Section: Why Does Liquid–liquid Phase Separation Occur In the Crystal...supporting
confidence: 72%
See 1 more Smart Citation
“…B 22 and k d measured under dilution are generally considered as predictors of high concentration behavior. Nevertheless, the high concentration behavior may differ from the behavior observed under dilution conditions because the “crowding” effect, i.e., increased opportunities for molecular interactions, deviations from thermodynamic ideals, and higher order interactions (e.g., B 23 , B 222 ), can significantly alter the net protein–protein interaction. , On the basis of the experimental observation of LLPS in the nucleation region, the authors suggest that it is likely that only a small number of protein molecules distributed at the droplet interface can experience protein–protein short-range attraction interactions induced by local environmental factors, without affecting the average B 22 value …”
Section: Why Does Liquid–liquid Phase Separation Occur In the Crystal...supporting
confidence: 72%
“…With the passage of time, the anisotropic interaction may be the reason for the evolution of the system from a phase separation state to a reversible aggregation state. In this case, LLPS is presumed to be metastable during nucleation. ,, However, when Mastropietro et al studied the crystallization of anti-CD20 (full-length monoclonal antibody) in a PEG400/Na 2 SO 4 /H 2 O system near LLPS, they found that second virial coefficient B 22 (positive value means repulsive interaction, negative value means attractive interaction) was not associated with protein interaction. The authors explain that in a complex mixture containing several components, the B 22 value cannot predict the LLPS since it may be associated with the protein-free polymer–salt phase separation.…”
Section: Why Does Liquid–liquid Phase Separation Occur In the Crystal...mentioning
confidence: 99%
“…Moreover, previous studies on Anti-CD20 crystallization showed that when an LLPS occurs in the crystallization solution, the nucleation of mAbs crystals occurs at the same moment. 32 , 45 These two phenomena being closely correlated, we assume the occurrence of one triggers the occurrence of the other, making it hard to discriminate which phenomenon is actually detected when the light transmission through the sample reduces.…”
Section: Discussionmentioning
confidence: 99%
“…Static light scattering measurements (Zetasizer Nano ZS instrument, Malvern Panalytical, Malvern, UK) were performed on Alg and AlgCF water solutions with a concentration between 0.1 and 5.0 mg mL −1 in order to determine the average molecular weight [ 69 ]. All the solutions were filtered using a 0.22 μm filter (Millex ® -GV syringe-driven filter unit, Merck/Sigma Aldrich, Darmstadt, Germany), and then placed in quartz cuvettes.…”
Section: Methodsmentioning
confidence: 99%